ECOLOGICAL CONSCIOUSNESS AS A FACTOR OF SUSTAINABLE DEVELOPMENT: A PHILOSOPHICAL AND PSYCHOLOGICAL ANALYSIS - Dildora Abdurakhmanovna Makhamova (Bright Mind Publishing, 2025)
This article investigates ecological consciousness as a key factor in achieving sustainable development, emphasizing its philosophical and psychological foundations. It analyzes how awareness and attitudes toward environmental issues are shaped by cognitive, cultural, and moral dimensions of human behavior. Drawing on interdisciplinary perspectives, the study explores the interplay between personal responsibility, collective ecological thinking, and global sustainability. Particular attention is given to the context of Uzbekistan, where environmental challenges require a deeper internalization of eco-values. The article advocates for educational and social strategies that cultivate ecological mindfulness as a necessary condition for fostering long-term ecological balance and ethical environmental governance.
Keywords: Ecological consciousness, sustainable development, environmental ethics, eco-psychology, ecological education, environmental behavior, moral responsibility, green thinking, cognitive awareness, eco-philosophy, environmental values, ecological culture, global sustainability, ecological identity.